Metamorfoze, the National Preservation Programme for Libraries in the Netherlands: Results and Pespectives - Schouten, Dennis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Metamorphosis: a word that means change but it also means keeping something from the original. Maybe even keeping the essence of that original. You can find metamorphosis in the classics, in literature, in art and, of course, in life itself: the changing of a caterpillar into a butterfly. In the Dutch language the word is spelled „Metamorfose”. The most famous late-nineteenth century author of the Netherlands, Louis Couperus, used an onorthodox way of spelling. His semi-autobiographical novel „Metamorfoze” with a „Z” which deals with the changes in an artist’s life was published in 1897. br> Exactly one hundred years later the Dutch National Preservation Programme was launched. And we decided to name it after this novel. The programme is all about change: from acid paper to microfilm or digital image, but it is also about keeping things from the past, preserving them. So the title of this nineteenth century novel seemed appropriate. And the Z could serve as an eyecatcher. This paper presents an overview of the programme, focusing on the following issues: • selection and setting priorities • method • approach • accomplishments (and setbacks) 1997-2000 • the second phase 2001-2004